Dopamine-secreting phaeochromocytomas and paragangliomas: clinical features and management - Foo, S.H.; Chan, S.P.; Ananda, V.; Rajasingam, V. (Stamford Publishing Pte Ltd / Singapore Medical Association, 2010)
Most functional phaeochromocytomas/paragangliomas produce noradrenaline and/or adrenaline. Those that produce dopamine are rare. We describe the distinguishing clinical features of dopamine-secreting phaeochromocytomas and paragangliomas from those that secrete noradrenaline/adrenaline and the impact on their management. We present a case of a dopamine-secreting paraganglioma from our institution and review 14 case reports of dopamine-secreting phaeochromocytomas/paragangliomas published between 1984 and 2008. As observed in the literature, 80% of the tumours were extra-adrenal. Most patients presented with non-specific symptoms or mass effect without the classical presentation of catecholamine excess. The majority were diagnosed with urinary or plasma dopamine. Five patients had malignant tumours and 12 patients underwent surgical resection of the primary tumours. Unlike noradrenaline/adrenaline-secreting phaeochromocytomas/paragangliomas, dopamine-secreting tumours lack a classical presentation, are extra-adrenal and have a higher malignant potential. A routine inclusion of urinary or plasma dopamine as part of catecholamine screening in all suspected phaeochromocytomas and paragangliomas is recommended.